Guide to Nigerian taxes : covering all aspects of direct and some indirect taxes - Farayola, G. O. (Ikeja, Lagos State, Nigeria : Allcrowns Nigeria, 1987)
This book examines the various types of taxation and its principles in Nigeria.
Accompanied by: Supplement to Guide to Nigerian taxes ([6] p.)
oo 30/08/2018, ijb, 27/03/2019
Loans
Keywords: Taxation; Nigeria